Rural-urban differences in adult life expectancy in Indonesia: a parametric g-formula-based decomposition approach - Sudharsanan, Nikkil; Ho, Jessica Y. (Epidemiology, 2020)
BACKGROUND: Evidence on rural-urban differences in adult mortality in low- and middle-income countries (LMICs) is limited and mixed. We examined the size of and factors contributing to rural-urban life expectancy differences among adults in Indonesia, the third most populous LMIC. - METHODS: Data come from the 2000, 2007, and 2014/2015 waves of the Indonesian Family Life Survey, a population-representative longitudinal study with mortality follow-up. We used Poisson regression and life tables to estimate rural-urban differences in life expectancy among 18,867 adult respondents ≥30 years. We then used a novel g-formula-based decomposition to quantify the contribution of rural-urban differences in blood pressure (BP), body mass index (BMI), and smoking to life expectancy differences. - RESULTS: Compared with urban adults, life expectancy at age 30 was 2.2 (95% confidence interval [CI] = 0.4, 3.9) years higher for rural men and 1.2 (95% CI = -0.4, 2.7) years higher for rural women. Setting the BMI and systolic BP distribution equal in urban and rural adults reduced the urban mortality penalty by 22% for men and 78% for women, with the majority of this reduction coming from the contribution of rural-urban differences in BMI. Smoking did not contribute to the urban mortality penalty for either men or women. - CONCLUSIONS: Adult life expectancy is lower in urban than in rural areas in Indonesia and we estimate that this difference is partly related to differences in BMI and systolic BP.